Radical Feminism of Natalie Artemis' Character in Monster Hunter Film - F. Sandro Asshary; Fatimah Muhajir; Ririn Setyowati (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
Feminism issues are often radically depicted in literary works, especially in a film today. Filmmakers emphasize these issues to raise women’s awareness about the oppression that might happen to them. This radical movement happens because they try to create an idealistic society for women. From this premise, radical feminism was born because the previous movement could not undo the women’s oppression as time goes throughout the decades. Adjusting to the patriarchal system, women are often portrayed as unique and unusual to be treated as equal to men. This study aims to analyze the radical feminism of Natalie Artemis’ character in Monster Hunter film using Tong’s radical feminism and Petrie and Boggs’ characterization theories. This research used Uwe’s qualitative descriptive method and Mikos’ film analysis theory. The researcher confirms that Natalie Artemis’ character is portrayed as a radical feminist through radical libertarians and radical cultural feminists’ ideas in the Monster Hunter film. These ideas are portrayed through Natalie Artemis’ androgynous appearance and gender portrayal.